EFEKTIVITASPENERAPAN KURIKULUM 2013 DALAM MENINGKATKAN KARAKTER PESERTA DIDIK KELAS VIII MELALUI MATA PELAJARAN AKIDAH AKHLAK DI MTS.MUHAMMADIYYAH CERENTI - Setri Arianti; Sarmidin Sarmidin; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
The background of this research is the era of globalization which is characterized by changes in competent character, social, cultural, educational and educational personnel. The 2013 curriculum policy is an innovation made by the government to improve the quality of education, the 2013 curriculum offers new concepts and ideas that put forward soffskill and hardskil to change education towards a betterThis study aims to test the effectiveness of the implementation of the 2013 curriculum in enhancing the character of VIII grade students through the subjects of the Islamic creed of MTs.MuhammadiyyahCerentiThis research is a quantitative study, the population of this study is all students of MTs.Muhammadiyah Cerenti, the sample in this study amounted to 35 people, students of class VIII and 1 moral teacher, the data collection was done by observation, interviews and documentation and analysis techniques the data uses descriptive statisticsBased on the results of the study, it can be concluded that the implementation of the 2013 curriculum in improving the character of students of class VIII through the subjects of the Islamic Morals. and observations of students in the first observation which reached only 32.3%, the second observation only 32.3% and the third observation only 41.17%.Even though they have experienced an increase in the level of implementation of the 2013 curriculum in improving the character of students of class VIII through moral subjects in MTs.MuhammadiyyahCerenti This has not been effective